Improving Shotcrete Application Through In-House Training and Field Support for Nozzlemen: A Case Study - SME Annual Meeting 2025 - Doandy Yonathan Wibisono (Society for Mining, Metallurgy & Exploration, 2025)
Shotcrete is a versatile and widely utilized rock support material in mining and civil engineering projects due to its adaptability, strength, and efficient application. It immediately stabilizes rock surfaces, effectively controlling loose materials and preventing rockfalls in underground excavations. This paper focuses on assessing and analyzing data from observations of nozzlemen (shotcrete sprayers) during primary ground support activities in an underground mine. The study highlights the importance of nozzlemen’s skills in ensuring the quality of shotcrete application, which is critical for underground mining operations’ structural integrity and safety. A comprehensive training program and field support were implemented to enhance the nozzlemen’s proficiency. The training set covered theoretical knowledge and practical techniques to improve shotcrete application daily. Proficiency improvement was assessed using quantitative metrics, with rebound percentages decreasing by 5–14% as nozzleman competency increased. The results of this initiative showed significant improvements in shotcrete quality, including increased efficiency, reduced waste, and fewer reworks or rehabilitations. The findings aim to contribute to a broader understanding of best practices in shotcrete application and nozzlemen training, ultimately enhancing ground support application measures in the mining industry.